Targeted grazing for the restoration of sub-alpine shrub-encroached grasslands - Probo, Massimiliano; Pittarello, Marco; Lonati, Michele; Lombardi, Giampiero (Italian Journal of Agronomy, 2016)
The decline of agro-pastoral activities has led to a widespread tree and shrub-encroachment of former semi-natural meso-eutrophic grasslands in many European mountain regions. Temporary night camp areas (TNCA) and mineral mix supplements for targeted cattle were arranged over shrub-encroached areas to restore grassland vegetation within the Val Troncea Natural Park (Italy). From 2011 to 2015, their effects on vegetation structure and pastoral value of forage were assessed along permanent transects. Four years after treatments, both practices were effective in reducing the shrub cover and increasing the cover and average height of the herbaceous layer, but changes were more remarkable within TNCA. Moreover, the arrangement of TNCA decreased the cover of nanophanerophytes and increased the cover of graminoids and high quality species, as well as the overall forage pastoral value. In conclusion, TNCA were the most effective pastoral practice to contrast shrub-encroachment and increase herbage mass and forage quality of sub-alpine grasslands.